Perbaikan Kebijakan Tata Kelola Perguruan Tinggi Kedinasan - Wijayanti, Anis; Selawati, Bekti Ayu (Integritas : Jurnal Antikorupsi, 2020)
Formally TVET (Technical and Vocational Education and Training) under the ministry where the graduates will be recruited to become civil servants (PTK) hereinafter referred to as PTKL was originally intended to meet the internal needs of the ministry/non ministry, but on the way developed into a collage that is not only aimed to fullfill internal needs but also the other of ministry/non ministry needs, sectors and public, the developments have not been followed by adequate regulatory and governance devices so that on the one hand as the increasing of PTKL increases the burden of the budget and on the other hand is potentially an overlap with higher education under the ministry that overtakes the higher educational. This research is a qualitative study that captures the existence of PTKL with a qualitative methodology that is a review of regulation, field review and interviewees and/or related experts. The findings of the problem in this research including current regulations are already irrelevant to the actual condition in the field, the absence of the raw criteria of the establishment of higher education vocational (PTKL), weak cooperation PTKL with the market/working industry, budget tagging issues and internal governance.